(untitled) (INNOVATIVE ECONOMY, 2025)
Chaikovskyi Ye.Ya. MODEL FOR ASSESSING AND FORECASTING THE FINANCIAL STABILITY OF THE BANKING SYSTEM OF UKRAINE Purpose. The aim of the article is to develop a model for assessing the financial stability of the banking system based on the integral financial stability index, which will contribute to maintaining the economic security of the state, as well as the application of the scenario forecasting method to take into account various risks and uncertainties affecting the stability of the banking system. Methodology of research. The following methods were used during the study: the indicator normalization method – to bring the indicators to a single scale (0; 1); the expert assessment method – to determine the weighting coefficients; the weighted average index method – to calculate the integrated financial stability index; the comparative analysis method – to determine the optimal ranges for each indicator; the statistical method – to analyse the variability of indicators over the years, identify trends and correlations between different elements of financial stability; the generalization method – to form the main results. Findings. The integrated financial stability index (IFS) is considered as an important tool for assessing and modeling the resilience of the banking system to economic and financial shocks. The methodology for calculating the IFS is presented, which includes five stages: selection of key financial stability indicators, normalization of indicators, determination of weight coefficients, calculation of the integrated indicator, and classification of the level of stability of the banking system. Based on this methodology, the IFS was calculated for the period 2019-2024 and the forecast for 2025-2030 under three scenarios (pessimistic, baseline, and optimistic). The results indicate the effectiveness of using scenario analysis to predict the stability of the banking system, which allows taking into account various risks and economic factors, as well as assessing the system’s ability to respond to changes in the economic environment. Originality. The application of the integrated financial stability index of the banking system as an important tool for assessing and modeling financial stability, as well as the scenario forecasting method, which allows taking into account various risks and uncertainties affecting the stability of the banking system, has been further developed. Practical value. The results of the conducted research provide a deep understanding of the tools for assessing and modeling financial stability. In particular, the results contribute to improving the policy of the NBU and other state bodies regarding the timely identification of problems in the banking system and making informed decisions to support the stability of the financial sector. The application of the scenario forecasting method allows assessing future risks and uncertainties that may affect financial stability, as well as developing strategic plans to strengthen the system under different economic scenarios. This makes it possible to respond more effectively to possible economic shocks and adapt macroprudential regulation policies, ensuring the stability of banks and the stability of the economy as a whole. Key words: financial stability index, banking system, macroprudential indicators, capital ratios, liquidity, credit risk ratios, return on assets, return on capital, normalized values, integrated values.